Surgical Margins After Computer-Assisted Mandibular Reconstruction: A Retrospective Study - Crosetti, Erika; Succo, Giovanni; Battiston, Bruno; D'Addabbo, Federica; Tascone, Martina; Maldi, Elena; Bertotto, Ilaria; Berrone, Mattia (Frontiers in Oral Health, 2022)
Purpose: The use of virtual surgical planning in head and neck surgery is growing strongly. In the literature, its validity, accuracy and clinical utility for mandibular reconstruction are widely documented. Virtual planning of surgical bone resection and reconstruction takes place several days before surgery and its very sensitive nature can negatively affect an intervention aimed at maximum precision in term of oncological safety. Methods: The study focuses on a retrospective evaluation of the surgical margins in 26 consecutive cases with oral cavity malignancy and who underwent computer-assisted mandibular resection/reconstruction guided by the different types of bone, periosteal and peri-mandibular tissue involvement. The goal was to analyze the strategic and technical aspects useful to minimize the risk of positive or close margins and to vary the reconstructive strategy in the case of intraoperative findings of a non-radical planned resection. Results: No intraoperative or perioperative complications occurred. In 20 patients, virtual surgical planning permitted mandibular reconstruction to be performed using composite fibular free flaps, characterized by high accuracy and negative bone margins. In the remaining 6 patients, also virtually planned but otherwise reconstructed due to poor general condition (advanced age, severe comorbidity), negative bone margins were obtained. Intraoperative enlargement of the resection was carried out in one case and positive soft tissue margins were observed in another case. Conclusion: The results were satisfactory in terms of oncological radicality and precision. The functional benefits and reduction in operating times, previously demonstrated in other articles also by the authors, seem to justify the side effects related to the risk of modifying the planned surgery. During virtual planning, the surgeons must bear in mind that an unexpected progression of the tumor or a limited planned resection will entail modifying the extent of the resection intraoperatively and nullifying the virtual planning on which the reconstruction was based. Further investigations are necessary to clarify all aspects of virtual surgical planning in this setting.